Modulation of Candida albicans virulence in in vitro biofilms by oral bacteria. (1st April 2019) - Morse, D.J.; Wilson, M.J.; Wei, X.; Bradshaw, D.J.; Lewis, M.A.O.; Williams, D.W.
Abstract: Candida ‐associated denture stomatitis presents as erythema of the palatal mucosa and is caused by biofilms containing the fungus Candida albicans that co‐reside with oral bacteria on the denture‐fitting surface. This study aimed to assess the effect of several frequently encountered oral bacteria on the expression of C. albicans virulence factors in in vitro polymicrobial biofilms. Biofilms containing C. albicans and selected bacterial species were grown on denture acrylic, and analysed by microscopy and by qPCR for expression of putative virulence genes. Candida albicans ‐only biofilms showed limited hyphal production. Hyphal development was significantly ( P < 0·001) increased when biofilms also contained four species of oral bacteria ( Streptococcus sanguinis, Streptococcus gordonii, Actinomyces odontolyticus and Actinomyces viscosus ), as was the expression of virulence genes ( P < 0·05). Importantly, inclusion of Porphyromonas gingivalis in the biofilm consortium resulted in significant ( P < 0·05) inhibition of virulence gene expression and production of hyphae. The in vitro expression of C. albicans virulence factors was modulated in polymicrobial biofilms. The complexity of this modulation was highlighted by the reversal of effects following introduction of a single bacterial species into a biofilm community. Significance and Impact of the Study: The impact of individual bacterial species on Candida albicans virulence highlights both the complexity of predicting infection mediated by polymicrobial communities and the potential for management through pro‐ or prebiotic therapy. The possibility to selectively modulate microbial virulence by addition of, or treatment with pro‐ or prebiotics avoids the use of conventional antimicrobial compounds, thus reducing the contribution to potential drug resistance. Understanding which bacterial species modulate virulence, and the mechanisms by which this occurs, particularly in biofilms, provides excellent foundations for further research questions, and the potential for novel clinical interventions.